Quality specifications for highway bridges: standardization and homogenization at the european level (COST TU-1406) - Casas, J. R. (2016)
Roadway bridges, being one of the most critical road infrastructures components, require regular maintenance actions. Therefore, it becomes important to define strategies to maximize societal benefits, derived from the investment made in these assets. Consequently, this investment should be planned, effectively managed and technically supported by appropriate management systems. For this purpose, authorities need to produce an asset management plan which should, not only define the goals to be achieved by exploiting the roadway bridge network, but also identify the investment needs and priorities based on a life cycle cost criteria. Additionally, a proper condition assessment based on pre-defined performance indicators of these assets must be conducted to support the decision-making process regarding their preservation. It is obvious that there is a large disparity in Europe regarding the way these indicators are quantified and how their goals are specified. Therefore, due to the considerable number of methodologies, arises COST Action “TU1406: Quality specifications for roadway bridges, standardization at a European level (BridgeSpec)” which aims to bring together, for the first time, both research and practicing community in order to accelerate the establishment of a European guideline and homogenization in this subject through Europe. This paper gives an overview of COST Action TU 1406, namely, its objectives, methodology and main deliverables.